Mediators of the association between nut consumption and cardiovascular diseases: a two-step mendelian randomization study - Ruizhe Wang; Jinfang Sun; Xiaojin Yu (Scientific Reports)
Abstract Previous observational studies have reported inconsistent associations between nut consumption and cardiovascular diseases (CVD). This study aims to identify the causal relationship between different types of nuts consumption and CVD, and to quantify the potential mediating effects of cardiometabolic factors. We utilized Genome-Wide Association Study (GWAS) data to assess the causal effects of nut consumption on CVD using two-sample Mendelian randomization (MR) and a two-step MR analysis. The inverse variance weighted (IVW) method indicated that processed (salted or roasted) peanuts were potentially and positively associated with ischaemic heart disease (IHD) (OR 1.4866; 95%CI 1.0491-2.1065). No causal relationships were found between nuts consumption and other CVD outcomes, including atrial fibrillation, angina, coronary atherosclerosis, coronary heart disease, IHD, myocardial infarction, subarachnoid hemorrhage, intracerebral haemorrhage and stroke. Both MR-Egger and median-based methods yielded similar results to IVW. Furthermore, in the two-step MR analysis, fasting insulin, low-density lipoprotein cholesterol and fasting blood glucose were identified as mediators in the potential causal relationship between processed peanuts and IHD, explaining 16.98%, 6.38% and 4.91% of the mediation, respectively. In total, these mediators accounted for 28.27% of the association between salted or roasted peanuts and IHD.